Hippocampal dynamics of synaptic NF-kappa B during inhibitory avoidance long-term memory consolidation in mice. (16th April 2015) - Salles, A.; Boccia, M.; Blake, M.; Corbi, N.; Passananti, C.; Baratti, C.M.; Romano, A.; Freudenthal, R.
Highlights: NF-kappa B is present at the synapses. Synaptic NF-kappa B is activated during memory consolidation. NF-kappa B may also have a local role at the synapses. Synaptic NF-kappa B translocates to the membranes during memory consolidation. Local NF-kappa B may recruit post-translational modifying proteins. Abstract: Since the discovery that long-term memory is dependent on protein synthesis, several transcription factors have been found to participate in the transcriptional activity needed for its consolidation. Among them, NF-kappa B is a constitutive transcription factor whose nuclear activity has proven to be necessary for the consolidation of inhibitory avoidance in mice. This transcription factor has a wide distribution in the nervous system, with a well-reported presence in dendrites and synaptic terminals. Here we report changes in synaptosomal NF-kappa B localization and activity, during long-term memory consolidation. Activity comparison of synaptosomal and nuclear NF-kappa B, indicates different dynamics for both localizations. In this study we identify two pools of synaptosomal NF-kappa B, one obtained with the synaptoplasm (free fraction) and the second bound to the synaptosomal membranes. During the early steps of consolidation the first pool is activated, as the membrane associated transcription factor fraction increases and concomitantly the free fraction decreases. These results suggest that the activation of synaptic NF-kappa B and its translocation to membranes are part of the consolidation of long-term memory in mice.